IMPLEMENTING “REAP” TECHNIQUE IN READING COMPREHENSION FOR SENIOR HIGH SCHOOL - Pratiwi, Rizky Silvia; Ardian, Fendi (Annual International Conferences on Language, Literature, and Media; No 1: 3rd AICOLLIM (Annual International Conference on Language, Literature, and Media), 2021)
Most students of Sekolah Menengah Atas Swasta Pesantren Sabilil Muttaqien (SMAS PSM) Plemahan were less interested in reading English, so they had low reading comprehension. This study focuses on implementing the Reading, Encoding, Annotating, and Pondering (REAP) technique and the effective model to improve students' reading comprehension. This research was a Classroom Action Research and carried out in two cycles. This study's subjects were students of class X from SMAS PSM Plemahan, consisting of 21 students. The data were collected from reading test scores, student and researcher observation sheets, and field notes. The results showed an improvement of the mean score, students' success percentage, and the observation sheet in the 1 st and 2 nd cycles, achieving the success criteria. The students were more interested in learning English, and it is easier to find the text's main idea. The research findings meant that this REAP technique was successful in improving students' reading comprehension. Thus, the teachers were necessary to apply this technique in the learning process by forming the class into groups to be more enthusiastic in learning English and improve their reading comprehension.